ANALISIS RESPON SEGMEN GEOGRAFIS TERHADAP PASAR KAGET DI KOTA BATAM - Jurnal Ilmiah Manajemen UPB (Universitas Putera Batam, 2017)
This study aims to determine consumer response based on geographical segments to the market shock in Batam City, especially in the nine districts that are in the geographic area of ​​Batam Island. Market segmentation is a concept that is very important in this life. In business activities, market segmentation is used for selecting target markets, looking for opportunities, undermine the leader segment of the market, formulate communication messages, serve better, analyze consumer behavior, and designing products. To analyze the response of various segments to the shock market in Batam used qualitative method with descriptive approach. Data analysis method is Model Analysis Spradley with departing from the broad focus of study and then find more widespread. Batam city composed of 12 districts in eight districts scattered as many as 25 shock markets. Geographically, the market is divided into geographic units as diverse as country, region, province, city, or neighborhood; while in this study, geographic units based on those districts. Geographically, all the shock market in the territory of Batam Island. Spreading shock market dominated by the District of Batu Aji with 10 shock market following the five District of Sekupang with shock market, while the District Sagulung four shock market and the District of Batam City as much as two shock market. For Districk of Nongsa, Batu Ampar, Bengkong, Sei Beduk, each one shock market, and the latter districts Lubuk Baja did not have a market shock at all.